1999
DOI: 10.1017/s0954579499002047
|View full text |Cite
|
Sign up to set email alerts
|

Attachment organizations in children with difficult life circumstances

Abstract: The purpose of this study was to use the Attachment Q-Set to create categories of attachment organization that were conceptually consistent with organizational categories derived from other attachment assessments, reliable, and valid. We were particularly interested in creating categories that would describe insecure attachment organizations in children from difficult life circumstances. Our sample of relationships included 3062 teacher-child relationships. Children ranged in age from toddlers to kindergartner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 7 publications
4
83
1
5
Order By: Relevance
“…Furthermore, results from this and other studies indicate protective effects of high-quality teacher-child relationships (e.g., Birch & Ladd, 1996;Howes & Ritchie, 1999). Educating teachers as to how to develop highquality relationships with children may provide strategies for teachers working with children who are at risk for lower levels of achievement.…”
Section: Educational Implicationsmentioning
confidence: 56%
“…Furthermore, results from this and other studies indicate protective effects of high-quality teacher-child relationships (e.g., Birch & Ladd, 1996;Howes & Ritchie, 1999). Educating teachers as to how to develop highquality relationships with children may provide strategies for teachers working with children who are at risk for lower levels of achievement.…”
Section: Educational Implicationsmentioning
confidence: 56%
“…Sample items include "I share an affectionate, warm relationship with this child" (closeness), "This child is overly dependent on me" (dependency), and "This child easily becomes angry with me" (conflict). The STRS is a widely used instrument of preschool-and elementary-aged children (e.g., Birch & Ladd, 1997;Howes & Ritchie, 1999;Skalická et al, 2015). Because we had no hypothesis regarding which aspect of the student-teacher relationship would be (differentially) affected by the parent-child This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Gene-؋-environment Interactionmentioning
confidence: 99%
“…This questionnaire assesses the affective quality of caregiving relationships in primary and secondary education and is used to determine teachers' perceptions of their relationships with individual children. Previous studies have examined teacher-child relationships in primary and secondary schools (Baker, 1998(Baker, , 2006, 1998Howes & Ritchie, 1999;Hughes, Cavell, & Jackson, 1999;Pianta, 1999). These studies consistently indicated that close relationships with teachers are associated with positive school adjustment.…”
Section: Teachers' Relationships With Typically Developmental Childrenmentioning
confidence: 99%